Equity in medical education: Addressing microaggressions and discrimination on the wards. (4th May 2022) - Sandoval, Raquel Sofia; Dunleavy, Spencer; Afolabi, Titilayo; Said, Jordan Taylor; Connor, Jade; Hossain, Azfar; Kassamali, Bina; Kienka, Tamina; Srinivasan, Maahika; Cheng, Anita; Ölveczky, Daniele; Chatterjee, Avik
Abstract: Purpose: Existing frameworks to address instances of microaggressions and discrimination in the clinical environment have largely been developed for faculty and resident physicians, creating a lack of resources for medical students. Methods: We implemented a workshop to prepare pre-clinical medical/dental students to recognize and respond to microaggressions. Participants in three cohorts from 2018 to 2020 completed pre- and post-workshop surveys assessing the prevalence of exposure to clinical microaggressions and the workshop's effect on mitigating commonly perceived barriers to addressing microaggressions. Results: Of 461 first-year medical and dental students who participated, 321 (69.6%) provided survey responses. Over 80% of students reported experiencing microaggressions, with women and URM students over-represented. After the workshop, participants reported significant reductions in barriers to addressing microaggressions and discrimination, including recognizing incidents, uncertainty of what to say or do, lack of allies, lack of familiarity with institutional policies, and uncertainty of clinical relevance. The workshop was similarly effective in-person and virtual formats. Conclusions: Most medical/dental student respondents reported experiencing microaggressions in the clinical setting, particularly female and URM students. Our workshop mitigated most perceived challenges to responding to microaggressions. Future interventions across institutions should continue to equip students with the tools they need to address and respond to microaggressions.